Electronic Games and their impact on children - Ameer Salah-Aldeen , Abdulrazaq; Zaman Ahmed Hrefish; Abbas Lateef Muhe-Aldeen (Genius Journals, 2022)
A video game can be enjoyed by children, adolescents, and adults of any age. The latest video games and gaming consoles often top people's wish lists and dinner table conversations. However, a new study suggests that playing violent video games may have long-term behavioral effects on some children. Young people all over the world can easily get their hands on violent video games. Because of this, children and adolescents are more susceptible to the negative effects of video games than adults (above 34 years of age). We all care about the health and well-being of our children.
Keywords: Electronic Games; Impact; Children